Appetite Suppression and Interleukin 17 Receptor Signaling Activation of Colonic Mycobiota Dysbiosis Induced by High Temperature and High Humidity Conditions - Guo, Yinrui; Guo, Hongya; Qiu, Lingyan; Fu, Yuanfei; Zhu, Xiangxiang; Zhang, Haiting; Wang, Jian; Chen, Diling (Frontiers in Cellular and Infection Microbiology, 2021)
The roles of microbiome on human physiology, emotion, disease, growth and development were undoubted, and we know that most of us have poor appetite on the high temperature and high humidity condition (HTHH), and the fungus loves this moist environment. Therefore, we assume that the colonic mycobiota may play an important role in affecting the host appetite under the HTHH; meanwhile, changes in humidity are also associated with the autoimmune diseases. Here, the mice were fed in a HTHH (T = 32 ± 2 °C, RH = 95%) using artificial climate box, 8 hour per day and last 21 days. The food intake, colonic fungus microbiome and metabolome of feces, and appetite regulators were monitored. Indicators of the interleukin-17 pathway was also examined. Results showed that the food intake and body weight were reduced, the colonic mycobiota and fecal metabolome were changed obviously by compared the control groups (T = 25 ± 2 °C, RH = 65%). The appetite related proteins of LEPT and POMC in hypothalamus were up-regulated (p < 0.05), and gene of NPY was down-regulated (p < 0.05), the expressions of PYY, O-GlaNAc and PAS staining in the colonic tissues were changed (p < 0.05); the expressions of IL-17 in colon were up-regulated. Correlation analysis of ‘microbiome -metabolomics’ showed that there was a stronger correlation between the colonic fungus and the sugar metabolism, we also found that some metabolites of cholesterol, tromethamine and cadaverine in fimo were increased obviously (p < 0.05). The significant elevation of characteristic fungi of Solicoccozyma aeria showed a trigger on appetite suppression and IL-17R signaling activation on some susceptible host, and disturbance effect the gut bacteria and fungi. All the results indicated that the gut mycobiota play an important role in the hypothalamus endocrine system to regulate the host appetite via gut-brain axis, and also play an indispensable role in the stability of gut microbiome and immunity, while most of the mechanism still need much more studies.